Single-cell analysis of dup15q syndrome reveals developmental and postnatal molecular changes in autism - Yonatan Perez; Dmitry Velmeshev; Li Wang; Matthew L. White; Clara Siebert; Jennifer Baltazar; Guolong Zuo; Juan Andrés Moriano; Songcang Chen; David M. Steffen; Natalia Garcia Dutton; Shaohui Wang; et al. (Nature Communications)
Abstract Duplication 15q (dup15q) syndrome is a leading genetic cause of autism spectrum disorder, offering a key model for studying autism-related mechanisms. Using single-cell and single-nucleus RNA sequencing of cortical organoids from dup15q patient-derived iPSCs and post-mortem brain samples, we identify increased glycolysis, disrupted layer-specific marker expression, and aberrant morphology in deep-layer neurons during fetal-stage organoid development. In adolescent-adult postmortem brains, upper-layer neurons exhibit heightened transcriptional burden related to synaptic signaling, a pattern shared with idiopathic autism. Using spatial transcriptomics, we confirm these cell-type-specific disruptions in brain tissue. By gene co-expression network analysis, we reveal disease-associated modules that are well preserved between postmortem and organoid samples, suggesting metabolic dysregulation that may lead to altered neuron projection, synaptic dysfunction, and neuron hyperexcitability in dup15q syndrome.